Contextualising the Eco-Campus Agenda in Islamic Higher Education: Insights from the Institutional Planning - Syaripah; Wahyuningsih, Wiwin Arbaini; Destriani (Al-Hayat: Journal of Islamic Education, 2025)
This study aims to examine the initial planning stages of Institut Agama Islam Negeri (IAIN) Curup's transformation into an environmentally conscious campus (Eco-Campus). This study addresses the gap in the implementation of sustainability concepts within religious higher education institutions in Indonesia. This study emphasizes the importance of integrating environmental awareness into institutional development strategies based on UI GreenMetric indicators. The study employed a descriptive qualitative approach with field studies conducted at IAIN Curup and relevant government agencies. Data collection techniques included interviews, observation, documentation, and literature review. Data analysis was conducted using a descriptive approach, fishbone diagrams, and a SWOT analysis to evaluate institutional readiness and planning strategies. The results indicate that although the campus's ecological and physical conditions support eco-campus development, stakeholders' understanding remains limited. There is a lack of valid and accurate data and the absence of integrated environmental education policies and programs. The majority of respondents still interpret eco-campus narrowly as a greening activity, not addressing the full aspects of sustainability. Limitations in this study include the limited availability of accurate environmental data and technological barriers common to institutions in developing countries. This limits the direct application of the research findings in the short term. This research provides an original contribution in the form of a local analysis of eco-campus readiness in Islamic educational institutions, a topic rarely studied. The results provide practical insights for integrating sustainability principles into campus governance and academic culture. These findings can inform further research and policy development at similar institutions.